The Enjoyable Physical Education Learning to Improve Students' Motivation and Learning Achievement - Fuaddi Fuaddi; Tomoliyus Tomoliyus; Pamuji Sukoco; Soni Nopembri (Lesya Ukrainka Volyn National University, 2020)
Topicality. The using of appropriate learning model is the key in creating an effective, conducive, and enjoyable learning. Therefore, the supporting of teachers' learning literacy model becomes a research field should be renewed and improved. Research Purpose. The purposes of this research are: (a) to know how peer teaching can give motivation and improve the learning achievement of students. (b) The things should be noticed in implementing the peer teaching method. Methods. The method used in this research was literature study using research steps by Wolfswinkel et al. Research Result. The result of this research shows that the using of peer teaching learning model gives many academic benefits, one of them is the improvement of psychomotor aspect, cognitive aspect, and affective aspect of students. Besides that, another academic benefit obtained such as that learning model can train students' communication skill and also can elevate students' confidence which also can be obtained through the pear teaching learning model. From the analysis of all collected data, there are some recommendations. The peer teaching learning model can be used in every level of education. Peer teaching learning model will be more effective if accompanied by additional teaching media such as task card and other kinds of media. In many writings, the peer teaching learning method is often used in field practice learning which trains the psychomotor skill, but still can improve other domains such as cognitive and affective.